Perspectives of professionals on the safety and accessibility of aged care for Care Leavers and Forgotten Australians. (7th May 2021) - Browne‐Yung, Kathryn; O'Neil, Diana; Walker, Ruth; Corlis, Megan; Smyth, Alison; Putsey, Peter; Laver, Kate E.; Fernandez, Elizabeth; Cations, Monica
Abstract: Objectives: Little is known about how prepared the aged care system is to meet the specific needs of Care Leavers and Forgotten Australians. We explored service provider and advocate perspectives about the barriers and facilitators for appropriate and safe care for this group. Methods: Three focus groups with sixteen professional stakeholders examined the ways aged care support is accessible and inaccessible for Forgotten Australians. Results: Participants noted structural and organisational features that act as barriers to best practice aged care. It was perceived that funding models and processes provide insufficient opportunity to develop trust with professionals and access tailored care. Once engaged with aged care services, the sector lacks the psychological literacy required to tailor care to manage the complex needs and preferences of Forgotten Australians. Conclusions: Systemic and organisational change that promotes increased flexibility, trauma‐informed care and non‐residential housing options will improve the safety and accessibility of aged care for Forgotten Australians.